Desain Model Akselerasi Manajemen Sampah Sekolah Dasar sebagai Upaya Pembentukan Sekolah Berbudaya Lingkungan dan Pemberdayaan Ekonomi - Dwipasari, Lita (Jurnal Manajemen dan Kewirausahaan, 2016)
Bank SampahÂ in Malang is an arm of government to manage waste. The more increasing number of quality garbage collected, the greater the customer’s account at the Bank. Bank SampahÂ will help meet the wasteÂ demandÂ Â ofÂ recycling plant. Elementary school is the customer target groupsÂ Bank Sampah Malang. They have many obstacles in its waste management activities. Bank SampahÂ and the Department of Education inÂ Malang has been providing direction and some facilities for waste management in elementary schools. This study was conducted to produce a acceleration model of waste management Elementary School. Making design through several phases: analysis of the situation (questionnaire, observation and documentation). Structured questionnaire based on analysis Input-Process-Output (IPO). Evaluation model made through brainstorming to generate empirical models. Socialization and accompaniment isÂ done at 3 elementary schools. Field testing is conducted through a quasi method because there are treatment methods for sample (Elementary School) . Final testing of this model is the descriptive analysis (changes of primary account numberÂ andÂ environmental changes of elementary school) and inferential analysis by performing the Wilcoxon paired sample test (for non-parametric statistics). https://doi.org/10.26905/jmdk.v4i2.1065